Crowdfunding Innovation In Village Tourism Development: A Sustainable Investment Model For Community Economic Improvement - Faizin, Moh.; Anggraini, Yulia; Ridwan, Mohammad (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2025)
The development of tourism villages is a crucial strategy for enhancing the economic well-being of rural communities, although limited capital often acts as a barrier. This study examines crowdfunding-based investment innovations as an alternative to traditional fundraising methods for tourism villages, using case study in Ketapanrame Village. The study focuses on tourism infrastructure financing, community empowerment, and business diversification rooted in local wisdom. Results show increased citizen participation, job creation, and accelerated inclusive economic growth in the village. Community funding through crowdfunding has proven effective with transparent mechanisms, community-based dividend distribution, and clear boundaries. In addition to strengthening sustainability, this model promotes direct community involvement in development. These findings are expected to serve as a reference for policymakers and investors to design more innovative, educational, and community-responsive tourism village funding schemes.